METTL3-VISTA axis-based combination immunotherapy for APC truncation colorectal cancer - Hui Wang; Yujie Zhang; Ling Wu; Liang Zhao; Hao Chen; Rui Bai; Jianghua Wu; Zetao Chen (Journal for ImmunoTherapy of Cancer)
Objective Although immune checkpoint blockade (ICB) therapy represents a bright spot in antitumor immunotherapy, its clinical benefits in colorectal cancer (CRC) are limited. Therefore, a new target for mediating CRC immunosuppression is urgently needed. Adenomatous polyposis coli (APC) mutations have been reported as early-stage characteristic events in CRC, but the role of truncated APC in the CRC immune microenvironment remains unclear and its clinical significance has yet to be explored.Design Adenocarcinoma formation in the colon of the APCMin/+ mouse model, which displays features associated with the translation of truncated APC proteins, was induced by azoxymethane/dextran sodium sulfate. Multiplexed immunohistochemical consecutive staining on single slides and flow cytometry were used to explore the activation of immune cells and the expression of the immune checkpoint V-domain immunoglobulin suppressor of T-cell activation (VISTA) in the CRC tissues of APCWT and APCMin/+ mice. The construction of truncated APC vectors and an initial subserosal graft tumor mouse model was employed to mimic the tumor microenvironment (TME) during APC mutation. Methylated RNA immunoprecipitation-quantitative PCR assays were performed to investigate the N6-methyladenosine (m6A)-dependent transcriptional regulation of hypoxia-inducible factor-1 alpha (HIF1α) by methyltransferase-like protein 3 (METTL3). Mettl3fl/fl vil1-cre+/− mice were used to demonstrate that targeting METTL3 is a mediator that mitigates the deleterious effects of the APC978∆-HIF1α axis on antitumor immunity. A chimeric VISTA humanized mouse model was used to evaluate the drug efficacy of the VISTA-targeted compound onvatilimab.Results We showed that APC978∆, a truncated APC protein, mediated overexpression of METTL3, resulting in m6A methylation of HIF1α messenger RNA and high expression of HIF1α. Furthermore, HIF1α promotes the migration of myeloid-derived suppressor cells to the TME by binding to the promoters of MCP-1 and MIF. In addition, HIF1α enhances the expression of the immune checkpoint VISTA on CRC cells, weakening tumor immune monitoring.Conclusions We elucidate that an underappreciated function of truncated APC in CRC is its ability to drive an immunosuppressive program that boosts tumor progression. Our work could provide a new perspective for the clinical application of immunotherapy in patients with CRC resistant to ICB therapy.